Geometric rectification technique for high resolution satellite data imagery using new geocentric-based datum - Rasib, Abd. Wahid; Omar, Abdullah Hisam; Amir Tan, Adhwa (Universiti Teknologi Malaysia, 2007)
Reference system is an important factor in order to verify and identify all measurement and data collection processes. The quality of the outputs is depending on how good a reference system is defined. The existing reference system is based on Rectified Skew Orthomorphic Projection (RSO), which is projected from Malayan Revised Triangulation (MRT) system. Many researches have been carried out to get a global coordinate system that suite with earth’s surface. A new datum also called geocentric datum, which is the origin referred to the origin of the earth, gives the best surface reference system for the entire world. In remote sensing applications, datum system (transformation) is important factor to gather spatial data for determination of coordinate location. By using the RSOgeodetic datum and RSOgeocentric datum as reference surfaces, geometry correction has been performed in terms to see the differences. The results shows that the average RMS errors is 0.2867 meter for north KL and 0.3306 meter for south KL from twelve checkm points that are measured. Then, the Z-test is carried out and the result shows that the errors of the checkpoints are accepted in 95 percent of confident level. From the comparison analyses between RSOgeodetic and RSOgeocentric coordinate datum, show that the coordinates changes happen as much as 194.0 meter to 195.0 meter.